Prevalence of occupational stress and workload among laboratory staff - Kumareswaran, Suriya; Muhadi, Siti Umairah; Sathasivam, Jeyanthini; Thurairasu, Vanitha (Intelektual Pustaka Media Utama, 2023)
Job stress is the detrimental physical and emotional responses that might occur when there is conflict between the expectations of a job and an employee's ability to meet those needs. Workplace stress is a global primary risk factor for worker health and diminishes workers’ motivation and productivity. A cross-sectional study was conducted involving 133 randomly selected laboratory staff from both private and government sectors in Johor, Malaysia. Descriptive analysis was conducted to establish the relationship between stress scores and the work burden of laboratory staff. The results indicate that 74% of the respondents have more than eighty percent stress scores. Cross tab demonstrates that there is an association between total staff and average patient daily and overall stress score (p-value <0.01). Pearson correlation shows a positive correlation between workplace environment and overall stress scores (p-value <0.01). The research indicates that work stress is a prevalent issue among laboratory staff. The well-being of laboratory staff is strongly connected to organisational success. Consequently, lab Staff, particularly those working in busy laboratories, should be highly prioritised.